2D-C3N4 encapsulated perovskite nanocrystals for efficient photo-assisted thermocatalytic CO2 reduction. Issue 5 (19th January 2022) - Bian, Hui; Li, Deng; Wang, Shengyao; Yan, Junqing; Liu, Shengzhong (Frank)
Abstract : A water-stable CsPbBr3 catalyst is designed using core–shell encapsulation of the perovskite nanoparticle by 2D-C3 N4 for photo-assisted thermocatalytic CO2 reduction by H2 O. The m-CN@CsPbBr3 heterojunction shows surprisingly high CO2 -to-CO yield. Abstract : Very recently, halide perovskites, especially all-inorganic CsPbBr3, have received ever-increasing attention in photocatalysis owing to their superior optoelectronic properties and thermal stability. However, there is a lack of study on their application in thermocatalysis and photo-thermocatalysis. Herein, we rationally designed a core–shell heterojunction formed by encapsulating CsPbBr3 nanoparticles with the 2D C3 N4 (m-CN) layer via a solid-state reaction (denoted as m-CN@CsPbBr3 ). A series of experiments suggest that abundant adsorption and active sites of CO2 molecules as well as polar surfaces were obtained by utilizing m-CN-coated CsPbBr3, resulting in significant improvement in CO2 capture and charge separation. It is found that the m-CN@CsPbBr3 effectively drives the thermocatalytic reduction of CO2 in H2 O vapor. By coupling light into the system, the activity for CO2 -to-CO reduction is further improved with a yield up to 42.8 μmol g −1 h −1 at 150 °C, which is 8.4 and 2.3 times those of pure photocatalysis (5.1 μmol g −1 h −1 ) and thermocatalysis (18.7 μmol g −1 h −1 ), respectively. This work expands the application of general halide perovskites and provides guidance for using perovskite-based catalysts for photo-assisted thermocatalytic CO2 reduction.